OLYMPIC EDUCATION THROUGH FRISBEE ULTIMATE SPORT (Fiep Bulletin - online, 2014)
This study conducted a qualitative research through a case study , based on the practice of sports based on ethics, fair play ( fair play ) , the Olympic Education and without the presence of a referee competition, and thus was possible formalize practical and theoretical reviews that resulted in the taking of necessary data to solve the central problematic: it is possible to generate actions related to the concept of fair play through Olympic education and sport in Physical Education? The educational project named Paulo Freire Tournament of Ultimate Frisbee was attended classes in the first year of high school. The overall objective of this project was to develop new sporting experiences, combining these experiences to the concepts of Olympic Education, fair play, moral and ethical, besides the choreographic work of organized cheerleading and the development of organizational capacity and consensus decision. Various educational actions related to ethics and ethics of sport, during the six months of the project were developed. At the end of the period and of the didactic and organizational actions, a tournament was held with the participation of mixed male and female teams. All disputes of eliminatory model occurred without the presence of a referee and there was no serious incident, the intervention of the organizers being required in 3 situations that have generated questions among participants and consequent lack of understanding in the field. We conclude that students are driven by many factors, not social action, and these can be modified, if worked by the school. The Olympic education is important for there to be a befitting civic education with social needs and the management of a social relationship less confrontational and less occurrence of disagreements.
Keywords: Sports Education; Physical Education; Sport Ethics; Olympic Education.